PERILAKU REMAJA PUTRI TENTANG PERSONAL HYGIENE SAAT MENSTRUASI - Anggraeni, Suci; Putri, Brita Arinda (Jurnal EDUNursing, 2023)
The problem of vaginal discharge is often experienced by women, especially adolescents after menstruation, to avoid these problems, good personal hygiene behavior is needed. This study aims to determine the relationship between the level of understanding and the role of parents in health education with adolescent girls' behavior in personal hygiene during menstruation. This research uses an analytical observational quantitative research design with a cross sectional approach design. The population in this study were 7th and 8th grade students at SMPN 3 Blitar City. The sample in this study amounted to 162 determined using the Stratified Random Sampling technique. The independent variable is the level of understanding and the role of parents in health education, while the dependent variable is the behavior of young women. Data were collected by questionnaire, bivariate analysis using ordinal regression test. From the results of the study, it is known that most students in understanding personal hygiene during menstruation are good, as many as 101 students (59%). The role of parents as educators is mostly in the good category, as many as 83 students (49%). Personal hygiene behavior during menstruation is mostly in the sufficient category, namely as many as 74 students (44%). The results showed that there was a relationship between understanding and personal hygiene during menstruation with a p value of 0.000 (p <0.05) and there was a relationship between the role of parents and personal hygiene during menstruation with a p value of 0.002 (p <0.05). Personal hygiene understanding and the role of parents affect personal hygiene behavior during menstruation. With a good understanding of adolescents and supported by the role of parents as educators, adolescents will apply personal hygiene properly and correctly. Keywords: Understanding, Role of parents, Behavior, Personal hygiene